Analisis Konsep Peningkatan Performance Perencana Melalui Pengelolaan Kinerja Pegawai Pada Kementerian Agama - Hartawan, Lalu Kiagus (Fakultas Ekonomi Universitas Gresik, 2023)
Planners are one of the State Civil Apparatuses who spearhead the progress of an institution because it relates to the main tasks and functions of development planning. In this regard, ASN performance management is regulated using the Regulation of the Minister of State Apparatus Empowerment and Bureaucratic Reform of the Republic of Indonesia Number 6 of 2022 concerning Management of the Performance of State Civil Apparatus Employees, but the implementation of these rules will cause obstacles both personal ASN planners and institutional constraints in fulfilling work unit targets. The purpose of this writing is to analyze and formulate the performance management of the ASN of the Ministry of Religion in accordance with the characteristics of employees so that they can meet the targets set in the work plan. This analysis was carried out using a qualitative approach, with descriptive data analysis. The results of the analysis for solving the problem are as follows. 1) Implementation of performance management rules not only requires increasing the competence of subordinates but also improving the function of leaders in terms of organizational communication. 2) Leaders must be able to take a personal approach appropriately according to the characteristics of employees. 3) The development of two-way communication in the performance dialogue. 4) All performance dialogs made must meet the SMART elements. 5) To avoid the subjectivity of the leader's assessment, the planner needs to make a DUPAK report. 6) There is an additional budget for performance guidance or performance counseling. Conclusion: performance management is the task and collaboration of all elements of employees in the institution.